FORMATION OF THE KABARDIN-BALKAR AUTONOMOUS REGION: MECHANISMS, PHASES, SIGNIFICANCE - BOROV, A.Kh; KAZHAROV, A.G. (Kavkazologiya, 2021)
In 2022, the celebration of the 100th anniversary of the formation of the Kabardin-Balkar Republic will take place. At the turn of the 1980–1990s. the historical experience of the early 1920s. and, above all, the circumstances of the creation and the institutional structure of the Kabardin-Balkar Autonomous Region were at the center of ethno-political collisions. The views on these issues that took shape at that time are still latently present in the public consciousness and are periodically updated in the political statements of individual public organizations. The subject of the proposed article is the political events in the region of the Central Caucasus (Terek Oblast, Gorskaya ASSR, Kabarda and Balkaria), which unfolded after the end of the civil war and the establishment of Soviet power in March 1920, and ended with the institutionalization of the system of power of the Kabardin-Balkar Autonomous Oblast in December 1922. The purpose of the study is to present a fairly complete, chronologically ordered picture of political events, struggles and decisions on the basis of systematization and analysis of documentary material, which makes it possible to reveal the mechanisms, identify the stages and assess the significance of creating a united Soviet autonomy for the Kabardian and Balkarian peoples. The novelty of the approach lies in the fact that the work is performed in the genre of documentary chronicle, aimed at but possibly complete and "dense" coverage of the course of events over the course of three years – from March 1920 to December 1922. Analysis and generalization of the involved material are included in the final section. The materials considered in the article show that the creation of the Kabardin-Balkar autonomy was not a one-time act, but a process that had as its content the coordination of the national interests of Kabarda and Balkaria and the development of a common form of their institutionalization.